A European Organisation for Research and Treatment of Cancer phase III trial of adjuvant whole-brain radiotherapy versus observation in patients with one to three brain metastases from solid tumors after surgical resection or radiosurgery: quality-of-life results - Soffietti, Riccardo; Kocher, Martin; Abacioglu, Ufuk M; Villa, Salvador; Fauchon, François; Baumert, Brigitta G; Fariselli, Laura; Tzuk-Shina, Tzahala; Kortmann, Rolf-Dieter; Carrie, Christian; Ben Hassel, Mohamed; Kouri, Mauri; et al. (Journal of clinical oncology, 2013)
This phase III trial compared adjuvant whole-brain radiotherapy (WBRT) with observation after either surgery or radiosurgery of a limited number of brain metastases in patients with stable solid tumors. Here, we report the health-related quality-of-life (HRQOL) results. HRQOL was a secondary end point in the trial. HRQOL was assessed at baseline, at 8 weeks, and then every 3 months for 3 years with the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire C30 and Brain Cancer Module. The following six primary HRQOL scales were considered: global health status; physical, cognitive, role, and emotional functioning; and fatigue. Statistical significance required P ≤ .05, and clinical relevance required a ≥ 10-point difference. Compliance was 88.3% at baseline and dropped to 45.0% at 1 year; thus, only the first year was analyzed. Overall, patients in the observation only arm reported better HRQOL scores than did patients who received WBRT. The differences were statistically significant and clinically relevant mostly during the early follow-up period (for global health status at 9 months, physical functioning at 8 weeks, cognitive functioning at 12 months, and fatigue at 8 weeks). Exploratory analysis of all other HRQOL scales suggested worse scores for the WBRT group, but none was clinically relevant. This study shows that adjuvant WBRT after surgery or radiosurgery of a limited number of brain metastases from solid tumors may negatively impact some aspects of HRQOL, even if these effects are transitory. Consequently, observation with close monitoring with magnetic resonance imaging (as done in the EORTC trial) is not detrimental for HRQOL.